2007
DOI: 10.1111/j.1468-1293.2007.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid treatment of facial fat atrophy in HIV‐positive patients

Abstract: ObjectivesFacial lipoatrophy can be devastating for HIV-infected patients, with negative effects on self-esteem. In this study, we treated facial fat atrophy in the nasogenian area with hyaluronic acid (Restylane SubQ; Q-Med AB, Uppsala, Sweden). MethodsTwenty patients were included in the study. Treatment effects were evaluated at baseline, and at weeks 6, 24 and 52 using ultrasound, the Global Aesthetic Improvement Scale, the Visual Analogue Scale and the Rosenberg Self-Esteem Scale. ResultsMean (AE standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
3
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 27 publications
(34 reference statements)
3
40
3
3
Order By: Relevance
“…Twelve-month treatment results from this study have been reported earlier [14]. In the present study, we report longerterm efficacy, safety and durability data. …”
supporting
confidence: 79%
See 2 more Smart Citations
“…Twelve-month treatment results from this study have been reported earlier [14]. In the present study, we report longerterm efficacy, safety and durability data. …”
supporting
confidence: 79%
“…As a result of this, the gel can be injected in larger amounts and into deeper skin layers [13], an advantage given that HIV facial lipoatrophy typically involves larger atrophic surface areas than seen in the general population. The use of a more viscous type of hyaluronic acid for the treatment of HIV-associated lipoatrophy has only been described previously in two studies, both with a follow-up period of 12 months [14,15]. The aim of our study was to evaluate the efficacy, safety and durability of a large particle hyaluronic acid in the correction of facial lipoatrophy in HIV-infected patients over a 3-year period.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the patients, 11% reported facial lipoatrophy, while the doctors observed clinically detectable facial lipoatrophy in 15% of the patients. 37 …”
Section: Epidemiologymentioning
confidence: 99%
“…Le Perlane® (Q-Med, Uppsala, Suède) en contient 10 000/ml. Le Restylane Sub-Q® est un NASHA plus visqueux, plus épais et moins résorbable ; il contient 1000 particules de gel/ml [11,12]. Bien que l'AH et en particulier les NASHA soient théori-quement non-toxiques, plusieurs effets indésirables ont été rapportés [13][14][15][16].…”
unclassified